1x+4(1-x)=4x+1(1-x)

Simple and best practice solution for 1x+4(1-x)=4x+1(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x+4(1-x)=4x+1(1-x) equation:


Simplifying
1x + 4(1 + -1x) = 4x + 1(1 + -1x)
1x + (1 * 4 + -1x * 4) = 4x + 1(1 + -1x)
1x + (4 + -4x) = 4x + 1(1 + -1x)

Reorder the terms:
4 + 1x + -4x = 4x + 1(1 + -1x)

Combine like terms: 1x + -4x = -3x
4 + -3x = 4x + 1(1 + -1x)
4 + -3x = 4x + (1 * 1 + -1x * 1)
4 + -3x = 4x + (1 + -1x)

Reorder the terms:
4 + -3x = 1 + 4x + -1x

Combine like terms: 4x + -1x = 3x
4 + -3x = 1 + 3x

Solving
4 + -3x = 1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
4 + -3x + -3x = 1 + 3x + -3x

Combine like terms: -3x + -3x = -6x
4 + -6x = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
4 + -6x = 1 + 0
4 + -6x = 1

Add '-4' to each side of the equation.
4 + -4 + -6x = 1 + -4

Combine like terms: 4 + -4 = 0
0 + -6x = 1 + -4
-6x = 1 + -4

Combine like terms: 1 + -4 = -3
-6x = -3

Divide each side by '-6'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| (3x^3-4x^4)2x^2= | | -5x+3(1-x)=-3x+1(1-x) | | 70s+20r=3300 | | 4/8=6/n | | 2(62.5+-2y)+4y=125 | | |3x-1/4|=2 | | 2x+0(1-x)=-5x+3(1-x) | | 15xy/35yz | | 9x^2-24x-1=0 | | 5x+-4(1-x)=2x+0(1-x) | | 10z^7(6z+3z^4+4)= | | 0=7x^3-24x^2-16x | | 4y+2x=125 | | 1.6*4= | | 8-8x=8-15x | | 6z^4(10z^5-5)= | | 2x+7-8x=-5 | | 32+48x= | | (1/4)e•e^4x=e^5/6 | | x=log15/log3 | | r^2+9=16 | | L(1/4)e•e^4x=e^5/6 | | (4x)(2y+x)(2y-x)=180 | | -4x+3(1-x)=5x+1(1-x) | | -1-5w+2-7w= | | 10y=/5 | | (9w^3-10w^2+7)8w^4= | | y=x^2+10x+29 | | V+b=g | | 3x-8=-5x+12 | | 3x+4(1-x)=5x+2(1-x) | | 0=12w^2+17w-40 |

Equations solver categories